Photoresonance and conductivity of surface electrons on liquid 3He: Электроны над жидким гелием - Konstantinov, Denis; Monarkha, Yuriy; Kono, Kimitoshi (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
Resonance variations of the in-plane conductivity of surface electrons (SEs) over liquid 3He induced by microwave (MW) radiation of a fixed frequency are experimentally and theoretically studied for low temperature scattering regimes (T < 0.5 K). The system was tuned to resonance by varying the amplitude of the vertical electric field which shifts the positions of SE Rydberg levels. The line-shape change and reversing of the sign of the effect are found to be opposite to that reported previously for weak vertical electric fields. A theoretical analysis of conductivity of the SE system heated due to decay of electrons excited to the second Rydberg level by the MW explains well the line-shape variations observed. It shows also that shifting the MW resonance into the range of weak vertical fields leads to important qualitative changes in the line-shape of SE conductivity which are in agreement with observations reported previously.